THE IMPACT OF ENTREPRENEURSHIP ECOSYSTEM AND SUSTAINABLE DIGITAL INNOVATION ON BUSINESS PERFORMANCE (CASE STUDY OF 150 MSMES IN SINGARAJA, INDONESIA) - Rundu Padang, Rikky; Pramana Putra, Made; Regri Ferdianto, Jemmy; Prasetya Muttiwijaya, Gede Teguh; Artha Pratama, Putu Dio (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Technology digital development and globalization dynamics in recent decades have brought significant changes to the business landscape, especially in the micro, small, and medium enterprises (MSMEs) sector. In Indonesia, especially in developing areas such as Singaraja, Bali Province, the implementation of a digital innovation-based entrepreneurial ecosystem still faces various challenges. This study aims to analyze the impact of the entrepreneurial ecosystem and sustainable digital innovation on business performance in Singaraja, Indonesia. This study uses a quantitative approach with purposive sampling with a survey method of 150 MSMEs. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study indicate that the entrepreneurial ecosystem has a positive and significant effect on sustainable digital innovation and business performance. These findings underline the importance of building a sustainable digital innovation-based business ecosystem to improve the competitiveness of MSMEs in the digital era. However, practical implications and future research directions need to be discussed in depth.